Evaluation of Biochemical and Epigenetic Measures of Peripheral Brain-Derived Neurotrophic Factor (BDNF) as a Biomarker in Huntington’s Disease Patients - Gutierrez, Ashley; Corey-Bloom, Jody; Thomas, Elizabeth A.; Desplats, Paula (Frontiers in Molecular Neuroscience, 2020)
Huntington's disease (HD) is an autosomal-dominant neurodegenerative movement disorder that presents with prominent cognitive and psychiatric dysfunction. Brain derived neurotrophic factor (BDNF) plays an important role in the pathophysiology of HD, as well as other neurodegenerative and psychiatric disorders, and epigenetic alterations in the complex BDNF promoter have been associated with its deregulation in pathological conditions. BDNF has gained increased attention as a potential biomarker of disease; but currently, the conflicting results from measurements of BDNF in different biofluids difficult the assessment of its utility as a biomarker for HD.Here, we measured BDNF protein levels in plasma (n=85) and saliva (n=81) samples from premanifest and manifest HD patients and normal controls using ELISA assays. We further examined DNA methylation levels of BDNF promoter IV using DNA derived from whole blood of HD patients and healthy controls (n=40) using pyrosequencing. BDNF protein levels were not significantly different in plasma samples across diagnostic groups. Plasma BDNF was significantly correlated with age in control subjects but not in HD patients, nor were significant gender effects observed. Similar to plasma, salivary BDNF was correlated with age only in control subjects, with no gender effects were observed. Importantly, we observed significantly lower levels of salivary BDNF in premanifest HD patients compared to control subjects. Salivary and plasma BDNF levels were not significantly correlated with one another, suggesting different origins. DNA methylation at four out of the 12 CpG sites studied in promoter IV were significantly altered in HD patients in comparison to controls. Interestingly, methylation at three of these CpG sites was inversely correlated to the Hospital Anxiety and Depression Scale (HADS) scores. BDNF promoter methylation was not correlated with motor or cognitive scores in HD patients, and was not associated with sex or age in neither disease nor control groups.CONCLUSIONS: Our studies show that salivary BDNF is decreased, and BDNF promoter methylation increased, in HD subjects compared to controls. These findings suggest that 3 salivary BDNF measures may represent an early marker of disease and DNA methylation at the BDNF promoter IV, could represent a biomarker of psychiatric symptoms in HD patients.